Effect of finite element formulation type on blast wall analysis subjected to explosive loading - Ng, W.C.K. (Asian Research Publishing Network, 2017)
This study suggests relevant finite element (FE) formulation types for the numerical simulations of a stainless steel offshore blast wall subjected to seven (7) blast loading scenarios. These structures are typically modelled by solid and shell finite elements considering the thicknesses of the structural parts. The FE simulations have been conducted in LSDYNA and the results were validated by the experimental results by HSE 1. The influence of strain rate has been considered to assess the dynamic responses of the blast loaded structure. Recommended FE types were discussed based on statistical analyses, which would provide broad insights into the influence of FE formulations on the blast response as well as the selection of FE formulations. © 2006-2017 Asian Research Publishing Network (ARPN).